The diagnosis of sheep pulmonary adenomatosis by exfoliative cytology and bronchoalveolar lavage techniques and the comparison of results with histopathologic findings - Metin Münir Kıran; M. Kemal Çiftçi; Hüdaverdi Erer; Fatih Hatipoğlu; Mehmet Tuzcu (Eurasian Journal of Veterinary Sciences)
This study was undertaken to examine gross, histopathologic and cytologic findings, and to determine the clinic-pathologic diagnostic criteria of sheep pulmonary adenomatosis (PA). For this purpose, 2630 sheep lungs were examined at a local slaughterhouse in Konya, and PA was found in 102 cases (3,88 %). Grossly, in 74 of 102 cases lobular lesions in one or more lobes, and in 28 cases larger lesions in all lobes were seen. These lesions were firm, shiny grey-while in colour and had grey-white nodules of different size on cut surfaces. Histopathologic examination revealed proliferation and papillary projection of alveolar and bronchiolar epithelium and in some cases neoplastic nodules in bronchiolar lumina. In 6 cases (5,88 %) metastatic tumors were found in mediastinal lymph nodes. In 53 of 102 sheep 2-25 ml of nasal discharge or sputum was obtained. In 26 cases the cytologic examinations of sputum revealed groups or clusters and sometimes single neoplastic cells resembling neoplastic cells in histopathologica! sec-lions. Cytologic examinations of touch preparations and smears of bronchoalveolar lavage (BAL) fluid made from 102 cases showed groups of neoplastic cells rn all cases. Some neoplastic cells in sputum. BAL and touch preparations showed anisocytosis, anisonucleosis and occasional mitotic figures. In conclusion. PA is a low grade bronchiolo-alveolar carcinoma. It was suggested that BAL may be useful in the diagnosis of PA but cytologic examinations of spulum have limited value.